2019
DOI: 10.1029/2018pa003502
|View full text |Cite
|
Sign up to set email alerts
|

North Atlantic Upper‐Ocean Hydrography During the Mid‐Pleistocene Transition Evidenced by Globorotalia truncatulinoides Coiling Ratios

Abstract: We use the coiling direction of planktic foraminifer Globorotalia truncatulinoides from four sites in the North Atlantic Ocean to assess spatial changes in upper‐ocean hydrography during the mid‐Pleistocene climate transition. Core top sediments indicate that the left‐coiling (sinistral) variety dominates regions characterized by a deep permanent thermocline as is characteristic of the subtropical gyre (Ocean Drilling Program Sites 1058 and Deep Sea Drilling Project Site 607) while right‐coiling (dextral) test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 52 publications
3
11
0
Order By: Relevance
“…At Sites 1056-1059 G. truncatulinoides coiling ratios were determined from the 355-500 μm size fraction, and at Site 1063, we picked from the >250 μm fraction because abundances were generally lower. As suggested by Feldmeijer et al (2014), and also shown by Kaiser et al (2019), the different size fractions are comparable. Sample intervals were split until 100 tests could be counted.…”
Section: Methodssupporting
confidence: 73%
See 3 more Smart Citations
“…At Sites 1056-1059 G. truncatulinoides coiling ratios were determined from the 355-500 μm size fraction, and at Site 1063, we picked from the >250 μm fraction because abundances were generally lower. As suggested by Feldmeijer et al (2014), and also shown by Kaiser et al (2019), the different size fractions are comparable. Sample intervals were split until 100 tests could be counted.…”
Section: Methodssupporting
confidence: 73%
“…Molecular clocks indicate that this type may have split from its ancestor, type I, a sinistral form, as recently as 170 kyr ago (De Vargas et al, 2001). Down-core studies in the western subtropical Atlantic Ocean, however, have distinguished dextral from sinistral tests during the middle Pleistocene (Chaisson et al, 2002;Kaiser et al, 2019) suggesting that branching occurred earlier. The relative abundance of sinistral versus dextral tests in type II G. truncatulinoides was recognized in early paleocenographic studies as linked to specific water masses and environmental parameters (e.g., Ericson et al, 1954;Herman, 1972;Thiede, 1971).…”
Section: Globorotalia Truncatulinoides As a Paleoceanographic Proxy (mentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, G. truncatulinoides increases (decreases) in abundance when the thermocline is deeper (shallower) 19,21 . The coiling direction of G. truncatulinoides has been commonly used to reconstruct the upper water column strati cation 21,22 , although surface sediments from the Atlantic Ocean reveal that the distribution of both sinistral and dextral morphotypes of G. truncatulinoides are closely related to the subtropical gyres 23 , showing high abundance inside the gyres, where the thermocline is deeper, and being virtually absent to the north and south of the gyres, where the thermocline is shallower (Fig. 1a-c).…”
Section: Introductionmentioning
confidence: 99%